Gambaran Pemberdayaan dan Kesejahteraan Keluarga (PKK) dalam Meningkatkan Pemberdayaan Perempuan di Nagari Lunang Barat Kabupaten Pesisir Selatan - Gian Ratna Sari; Irmawita Irmawita (PAKAR Pendidikan, 2019)
The research was motivated by the phenomenon of the succeed of the group in Nagari Lunang Barat, Pesisir Selatan Regency. This evidence by the high attendance list and it has been seen also by the achievements which obtained. Researchers suspect that the causes of this can be seen from the amount of people who are participated and have a motivation possessed by women who are active in PKK organization. The purpose of this study is to describe PKK in enhancing women's empowerment in Nagari Lunang Barat, Pesisir Selatan district with the relation to 1) Pancasila’s implementation and practice guidelines, 2) mutual cooperation, and 3) cooperatives. The method used in this study is descriptive with quantitative approaches. The sample in this study was taken as 50% of the total population of 25 women in Nagari Lunang Barat, Pesisir Selatan district. The sampling technique is a random sampling. It is namely as the method of selecting the sample applied to the population that is based on a particular area. The technique of collecting data by using a questionnaire. While the data analysis techniqueuses of the percentage formula. From the results of the study, the researcher found that the associations related to the guidelines for the implementation and practice of Pancasila, mutual cooperation, and cooperatives are categorized as good. Based on theresults of thestudy, itis recommended that women continue to be able to maintain and increase their activity and to the management of the group to continue to be able to motivate women in learning, so that the abilities and positive attitudes of the women’s generation.